(untitled) (Journal of human and social sciences, 2015)
This research studies and investigates the issue of human organ transplantation from an Islamic jurisprudence perspective. It begins by analyzing the nature of a person’s right over their body and reviews juristic opinions on the legitimacy of using organs from a living or deceased person, focusing on the Sharia controls and conditions that must be met. The paper discusses detailed rulings on issues such as: organ selling, transplantation from the deceased, determining the criterion of death (brain death vs. cardiac and respiratory arrest), and transplantation in cases of legal punishments (Hudud) and retribution (Qisas). The research relies on evidence from the Holy Quran, the Prophetic Sunnah, and consensus (Ijma’), as well as major jurisprudential principles such as removing harm, necessities permitting prohibitions, and choosing the greater of two benefits. It concludes by permitting organ transplantation under precise conditions that preserve human dignity and prevent exploitation, while outright rejecting the sale of organs.